Review on the Research and Development of an Intelligent Gait Training System for Fall Prevention in the Elderly Based on Multimodal Feedback - Zhang, Huaying; Wang, Jingyuan; Cao, Wenmei; Ba, Ying (Scientific Journal of Technology, 2026)
The aging process of China's population is accelerating continuously, and falls among the elderly have become a core pain point in the fields of home-based elderly care and geriatric rehabilitation, with gait instability being the primary cause of falls. Traditional gait training equipment suffers from high costs, poor adaptability to home environments, and high feedback delays, making it difficult to meet the demand for inclusive elderly care. Focusing on the research and development of an intelligent gait training system for fall prevention in the elderly, this paper conducts a comprehensive review from the aspects of the correlation mechanism between falls and gait instability in the elderly, the research status of intelligent gait training equipment, the application of multimodal feedback technology in geriatric rehabilitation, and the hardware development based on flexible sensing and embedded technology. Integrating relevant research results retrievable from CNKI (China National Knowledge Infrastructure), it analyzes the current research hotspots and existing problems in this field, providing a reference for the research and development of low-cost, high-response and user-friendly home-based gait training equipment for fall prevention in the elderly. Meanwhile, it elaborates on the R&D value and application prospects of the intelligent gait training system based on multimodal feedback.